The adoption of competition law remedies in the resolution of unlawful administrative decisions in public procurement - Sanickson, Melissa Levia (University of the Witwatersrand, Johannesburg, 2023)
This research report analyses the highly regulated area of public procurement, the available remedies and the role of competition law remedies as a potential form of redress for unlawful administrative decisions in public procurement. The decision to award a tender qualifies as administrative action and is reviewable in terms of the Promotion of Administrative Justice Act, Act 3 of 2000 (PAJA). Setting aside an unlawful tender is a primary remedy, however, a court has the discretion to grant this order. The court’s discretion is founded on an analysis of various interests and the conclusion is based on the most practicable outcome. Where a court withholds its discretion to set aside the tender, the successful tenderer benefits from an unlawful process. In unlawful procurement processes, competition is almost always distorted and the successful bidder has a competitive advantage due to unlawful conduct. It is a constitutional requirement and necessary that public institutions apply a competitive procurement process. Remedies found in the Competition Act, Act 89 of 1998, are more favourable than allowing the successful bidder to continue to benefit from an unlawful process. This research report develops a case for the amendment of PAJA to include ‘anti-competitive conduct’ as a ground to review administrative decisions in public procurement. The amendment will permit the applicability of the Competition Act and the remedies found within this area of law
Submitted in partial fulfilment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2023
Keywords: Public procurement; Competition law remedies; Promotion of Administrative Justice Act; Unlawful tender; UCTD; SDG-11: Sustainable cities and communities